Apixaban Enhances Vasodilatation Mediated by Protease-Activated Receptor 2 in Isolated Rat Arteries - Villari, Ambra; Giurdanella, Giovanni; Bucolo, Claudio; Drago, Filippo; Salomone, Salvatore (Frontiers in Pharmacology, 2017)
Apixaban (APX) is a direct inhibitor of factor X (FXa) approved for prophylaxis and treatment of deep venous thrombosis and atrial fibrillation. Because FXa activates protease-activated receptor 2 (PAR-2) in endothelium and vascular smooth muscle, inhibition of FXa by APX may affect vasomotor function. The effect of APX was assessed in vitro, by wire myography, in rat mesenteric resistance arteries (MRA) and basilar arteries (BA) challenged with vasoconstrictors (phenylephrine, PE; 5-hydroxytryptamine, 5-HT), vasodilators (acetylcholine, ACh; sodium nitroprusside, SNP) or with the PAR-2 peptide agonist SLIGRL. APX (10 M) reduced the vasoconstriction to PE and 5-HT while did not change the vasodilatation to ACh or SNP. SLIGRL induced concentration-dependent vasodilation in pre-constricted arteries, that was reduced by incubation with the NO inhibitor NG-nitro-L-arginine (L-NNA) and abolished by endothelium removal. APX enhanced vasodilation to SLIGRL either in the presence or in the absence of L-NNA, but was ineffective in endothelium-denuded vessels. In preparations from heparin-treated rats (to inhibit FXa) APX did not change the vasodilation to SLIGRL. FXa enzymatic activity, detected in mesentery homogenates from controls, was inhibited by APX, whereas APX-sensitive enzymatic activity was undetectable in homogenates from heparin-treated rats. Immunoblot analysis showed that incubation of MRA or aorta with APX increased the abundance of PAR-2, an effect not seen in MRA from heparin-treated rats or in endothelium-denuded aortas. In conclusion, inhibition of FXa by APX increases vasodilatation mediated by PAR-2. APX may act by inhibiting PAR-2 desensitization induced by endogenous FXa. This effect could be useful in the context of endothelial dysfunction associated to cardiovascular diseases.